The Influence of Voltage and Frequency Variations on Insulation Quality of a High Voltage Cable - Kocatepe, Celal; Kumru, Celal Fadil; Ayaz, Ramazan; Arikan, Oktay; Akca, Hakan (IEEE, 2013)
Insulation quality issue has had a significant place in high voltage systems for long years. Especially for high voltage cables, which is one of the most crucial elements in power systems, the measurements of dissipation factor or tan delta has a great importance on the insulation life time. Besides, when the power system parameters such as frequency and voltage level are not steady, tan delta measurement values will also be changed. Therefore, tan delta and dielectric loss measurement should be realized in case of unsteady power system conditions to get more exact results. In this study, tan delta measurement of a 20,1/34,5 kV, single core high voltage cable is carried out. By changing the frequency and voltage level, dissipation factor, capacitance (C-s), insulation resistance (R-s) and dielectric losses (P-k) measurement values are obtained.
Keywords: Tan delta; dielectric loss; High Voltage (HV) cable; HV measurement; XLPE cable; Computer Science; Telecommunications